2016
DOI: 10.1007/s40430-016-0668-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of the cutting forces on micromilling of an aluminum alloy

Abstract: List of symbols A Uncut chip area, mm 2 a Specific cutting energy coefficient, MPa/mm 2 b Depth of cut, µm F Cutting force, N f Feed per tooth, mm/th k Specific cutting force, MPa/mm 2 m Empirical factors n Rotational speed, rpm r Radius, µm t Uncut chip thickness, µm V Cutting velocity, m/min z Number of teeth Greek symbols θ Angular position of the cutting edge, rad ϕ Critical angle, rad Subscripts c Relative to chip cm Relative to minimum chip e Relative to edge r Relative to radial res-max Relative to maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…During the milling process, the tool and the workpiece keep in continuous contact, friction and frictional heat generated in the relative motion play important roles in the surface quality of workpiece [ 41 ]. Moreover, the aluminum alloy is soft material, which makes it easy to stick to the tool during milling, and then results in an increase in the surface roughness [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the milling process, the tool and the workpiece keep in continuous contact, friction and frictional heat generated in the relative motion play important roles in the surface quality of workpiece [ 41 ]. Moreover, the aluminum alloy is soft material, which makes it easy to stick to the tool during milling, and then results in an increase in the surface roughness [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their research also found that machining time and feed rate have a significant impact on the surface roughness [9]. Campos et. al.…”
Section: Introductionmentioning
confidence: 87%
“…The results of the predictive model has been appropriated the results of experimental work very good. Campos et al, (2017) in their study, a model of a mechanical cutting force, which adapted 6351-T6 aluminum alloy in micro-milling process was applied, without regard to homogeneous grain characteristics and tool run-out. Cutting forces experimentally were analyzed, taking into account the different feed rates and cutting speeds.…”
Section: Cutting Force In Micro Millingmentioning
confidence: 99%